PENGARUH RASIO RISK-BASED BANK RATING TERHADAP RETURN SAHAM PERUSAHAAN PERBANKAN - Praditasari, Anggi; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the empirical influence of Risk-Based Bank Rating ratio to the stock return. The variables in this research are Risk Profile, Good Corporate Governance, Earnings, and Capital as the explanatory variable to the dependent variable i.e. stock return. The sample collection has been conducted by using purposive sampling method and 31 banking companies with the observation periods during 2012 until 2015 have been selected as samples, After 104 observations data have been obtained, 20 data have been obtained after outlier has been done. The source of the secondary data has been obtained from Indonesia tock Exchange. The data analysis technique has been carried out by using multiple linear regressions analysis, and the SPSS program 20. Based on the result of the analysis, it can be concluded that: Loan to Deposit Ratio (LDR), Operating Expenses on Operating Income (BOPO), Capital Adequacy Ratio (CAR) doesnât give any influence to the stock return of banking company. Return On Assets (ROA) give significant influence to the stock price of banking company.Keywords: Risk Profile, Good Corporate Governance, Earning, Capital, Stock Return